Size matters: Filamentous bacteria drive interstitial vortex formation and colony expansion in Paenibacillus vortex. Issue 12 (17th September 2013) - Vallotton, Pascal
<x xml:space="preserve">Abstract</x> The beautiful patterns formed by motile bacteria have always intrigued the curious (Ben‐Jacob et al., Eur. Phys. J. B 2008;65:315–322). The mechanisms underlying their formation are believed to play a role in a range of natural phenomena, including embryogenesis, animal behavior, and economics. There has been significant effort to develop tools for characterizing the behavior of individual cells within large populations of migrating bacteria; a prerequisite for studying self‐organization in this context (Garner, Mol. Micro. 2011;80:577–579). Here, I apply powerful computer vision methods to study P. vortex interstitial colony expansion. Quantitative observations show how exceptionally long bacteria play a catalytic role—both in vortex formation, which had to date remained somewhat mysterious—and in facilitating colony expansion. This highlights the functional importance of bacterial morphology in bridging the microscopic and macroscopic scales, and it reshapes our understanding of vortex‐forming bacteria. © 2013 International Society for Advancement of Cytometry